One-Step 18F-Labeling of Estradiol Derivative for PET Imaging of Breast Cancer - Hongbo Huang (Contrast Media & Molecular Imaging, 2018)
Positron emission tomography (PET) imaging is a useful method to evaluate in situ estrogen receptor (ER) status for the early diagnosis of breast cancer and optimization of the appropriate treatment strategy. The 18F-labeled estradiol derivative has been successfully used to clinically assess the ER level of breast cancer. In order to simplify the radiosynthesis process, one-step 18F-19F isotope exchange reaction was employed for the 18F-fluorination of the tracer of [18F]AmBF3-TEG-ES. The radiotracer was obtained with the radiochemical yield (RCY) of ~61% and the radiochemical purity (RCP) of >98% within 40 min. Cell uptake and blocking assays indicated that the tracer could selectively accumulate in the ER-positive human breast cancer cell lines MCF-7 and T47D. In vivo PET imaging on the MCF-7 tumor-bearing mice showed relatively high tumor uptake (1.4~2.3 %D/g) and tumor/muscle uptake ratio (4~6). These results indicated that the tracer is a promising PET imaging agent for ER-positive breast cancers.